Regional song dialects of the Ortolan Bunting Emberiza hortulana L. in Sweden - Åström, Gustav; Stolt, Bengt-Olov (Ornis Svecica, 1993)
During the period 1966—1990 we studied the occurrence of different song dialects of the Ortolan Bunting in Sweden. Song dialects were identified for more than 420 males from about 150 different localities. We found that two regional dialects, one Northern Swedish and one Central Swedish, were prevailing. The characteristics of these two dialects are shown on melograms with one curve for fundamental frequency and one curve for relative sound pressure. The dialects can be identified and the differences clearly heard in the field without technical means. The Northern Swedish dialect is predominant north of the province of Hälsingland and the Central Swedish dialect south of that province. The two dialects meet and “overlap” in Hälsingland. The picture is supplemented by the occurrence of individuals with the foreign dialect, both dialects or a mixed dialect.